EVALUASI KEBIJAKAN PENGEMBANGAN KURIKULUM DI MADRASAH ALIYAH AL HUDA PANGKALAN SUSU KABUPATEN LANGKAT - Khairani Nasution; Makmur Syukri; Syafaruddin Syafaruddin (STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
The purpose of conducting research at Madrasah Aliyah Al-Huda Pangkalan Susu is to determine the results of the evaluation of madrasah-based curriculum policies using the principles of effectiveness, efficiency, adequacy, equity and responsiveness and accuracy. evaluation must continue to be carried out in order to improve program content, implementation and evaluation itself towards future curriculum innovationsThis research is a qualitative research. Data collection techniques are carried out by interview, observation, document review. The results of the study indicate that the development of a madrasah-based curriculum at Madrasah Aliyah Nurul Huda has not been optimal due to the lack of facilities and infrastructure. Researchers suggest that teachers can still be creative and innovate even with limited facilities and infrastructure because the current independent curriculum development policy implies that teachers are able to teach freely. by optimizing one's own abilities and being able to be creative without limits so that they are able to explore and explore students' abilities so as to overcome and solve life's problems and be able to compete and exist in the world of work later.